The effect of zinc sulfide on phase transformation of ferrihydrite - Loan, Mitch; Parkinson, Gordon; Richmond, William; Parker, A. (Mineralogical Society of America, 2005)
The addition of ZnS particles to suspensions of ferrihydrite promotes the formation of the more crystalline phases goethite [a-FeO(OH)] and hematite (a-Fe2O3) at pH ~ 2-3 and 85 deg. C. This previously undocumented effect appears to arise from surface-mediated reduction of Fe3+ species to Fe2+ with associated dissolution of ZnS.